Municipal Approaches in Maine to Reduce Single-use Consumer Products - Wagner, Travis (Maine Policy Review, 2016)
Maine’s solid waste management hierarchy prioritizes reduction and reuse over recycling. While most municipalities in Maine have focused on increasing recycling, they have undertaken minimal efforts to specifically foster source reduction and reuse. In this paper, Travis Wagner examines the approaches adopted in Maine by the state and by municipalities to reduce the consumption of single-use consumer products including bans, fees, consumer education, choice architecture, and retail take back.